Young adult partner phubbing and relationship satisfaction: the mediating role of attachment anxiety and the moderating role of constructive conflict coping style - Han, Yichu; Li, Xin; Song, WeiLing; He, Yifan (Frontiers in Psychology, 2025)
IntroductionThis study investigates the association between young adult partner phubbing and relationship satisfaction, with a focus on the mediating role of attachment anxiety and the moderating role of constructive conflict coping styles (voice or loyalty). Understanding these dynamics is crucial for enhancing relationship satisfaction among young adults.MethodsA sample of 837 undergraduate students (376 male students; average age 21.02 ± 1.931 years) was recruited to complete questionnaires assessing young adult partner phubbing, relationship satisfaction, attachment anxiety, and constructive conflict coping styles. The data were analyzed to explore the mediating and moderating effects within the proposed model.ResultsThe findings revealed that young adult partner phubbing was negatively associated with relationship satisfaction. This relationship was mediated by attachment anxiety, indicating that higher levels of phubbing increased attachment anxiety, which in turn decreased relationship satisfaction. Additionally, the relationship between attachment anxiety and relationship satisfaction was moderated by constructive conflict coping styles, suggesting that individuals who employed voice or loyalty coping strategies experienced a less pronounced negative impact on their relationship satisfaction.DiscussionThis study enhances our understanding of the mechanisms through which partner phubbing affects relationship satisfaction. The findings highlight the importance of addressing attachment anxiety and promoting constructive conflict coping strategies to mitigate the negative effects of phubbing. Practical implications for improving relationship satisfaction among young adult partners are discussed, emphasizing the need for interventions that foster healthy communication and conflict resolution skills.